EVALUATION ON LANGUAGE ATTITUDE OF PRESIDENTIAL CANDIDATES IN THE DISCOURSE OF DEBAT CAPRES 2019: APPRAISAL ANALYSIS - Dian Marisha Putri (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
General Election in 2019 is considered as the biggest party in democracy; it was used as the source of data from the third and the fourth segment on March 30, 2019. They were then transcribed and analyzed by using appraisal pattern study based on three analyses: engagement, attitude, and graduation in the appraisal pattern attitude. The result of the research in DC discourse consisted of engagement, attitude, and graduation. The attitude pattern of the presidential candidates comes from personality and the ‘order’ of political parties. Negative attitude is conveyed in the forms of expressions in dissatisfaction, injustice, greed, ambition, moral messages, noble values, and generosity. The function of presidential candidate debate is in the series of democratic system. Positive attitude identified in the Presidential Debate discourse through the utterances of Presidential Candidate 1 and Presidential Candidate 2 was analyzed through their implicit and explicit expressions such as a) acting in the firm way, b) acting hesitatingly, c) patience, and optimistic, and d) attitude toward gender.